EMPLOYING THE BIM-BASED APPROACH TO ANALYZE AND IMPROVE THE QUALITY OF DETAIL CONSTRUCTION COST ESTIMATION ACCORDING TO NRM 2 AND SMPI - Emelia Purba, Sarah; Diandra, Nadia; Feng, Chung-Wei (Fakultas Teknik Universitas Tanjungpura, 2022)
Construction projects have become increasingly complicated and challenging to manage in recent years, especially in analyzing the quantity and cost estimation of construction work to get accurate results and overrun costs. The interdependence among different work items involved, such as architects, civil and electrical works, is one of the fundamental reasons. Besides that, the differences in standards used in analyzing the quantity and unit cost per work item made it more complicated. This study analyzed the existing modeling based on the measurement rules and unit cost standards to analyze the problem which has been explained above. Understanding the items was considered when examining the walls quantity to avoid missing information. In addition, measurement rules standards are utilized to calculate QTO, including NRM 2 standards from the UK and SMPI standards from Indonesia, to calculate the cost based on Indonesia standard SNI-AHSP. Furthermore, using visual programming Dynamo to analyze the quantity of wall works based on the required data, extract the data/information needed to calculate the cost based on unit cost standard, and check if the walls intersect with other elements to avoid excess quantity. Finally, using BIM technology based on standard measurement rules and overlapping element analysis to calculate the quantity and cost produced accurate quantity results and obtained the maximum cost detail per work item. Moreover, generate the information about the analysis results by utilizing the intelligent module to present the required information of the wall works, which improves the inadequacy of BIM. Indeed, it could save more time than calculating them manually and reduce human errors.